3D geomechanical modeling of the response of the Wilzetta Fault to saltwater disposal. Issue 6 (21st December 2021) - Hemami, Behzad; Masouleh, Shahla Feizi; Ghassemi, Ahmad
Abstract: From 2009 to 2017, parts of Central America experienced marked increase in the number of small to moderate‐sized earthquakes. For example, three significant earthquakes (~ M w 5) occurred near Prague, Oklahoma, in the U. S. in 2011. On 6 Nov 2011, an M w 5.7 earthquake occurred in Prague, central Oklahoma with a sequence of aftershocks. The seismic activity has been attributed to slip on the Wilzetta fault system. This study provides a 3D fully coupled poroelastic analysis (using FLAC3D) of the Wilzetta fault system and its response to saltwater injection in the underpressured subsurface layers, especially the Arbuckle group and the basement, to evaluate the conditions that might have led to the increased seismicity. Given the data‐limited nature of the problem, we have considered multiple plausible scenarios, and use the available data to evaluate the hydromechanical response of the faults of interest in the study area. Numerical simulations show that the injection of large volumes of fluid into the Arbuckle group tends to bring the part of the Wilzetta faults in Arbuckle group and basement into near‐critical conditions. Key Points: We constructed a 3D fully coupled geomechanical model to study the response of the Wilzetta Fault to saltwater disposal. Injection in either a semi‐restricted zone or an infinitely open one caused fault instability in 2001 (10 years before the main events in 2011). Continuous injection in a fully bounded zone caused pore pressure increase, and led to fault failure in 2011.